Bodily self‐disturbance in schizophrenia‐spectrum populations: Introducing the Benson et al. Body Disturbances Inventory (B‐BODI). Issue 1 (26th March 2019) - Benson, Taylor L.; Brugger, Peter; Park, Sohee
Abstract: Anomalous or weakened sense of self was central to early theories of schizophrenia. Recent studies have also documented disturbances in body ownership and increased susceptibility for dissociative experiences, such as the out‐of‐body experience in individuals with schizophrenia, but further research is necessary to clarify components of bodily self‐disturbances in the schizophrenia spectrum, and the stability of these experiences over time. With respect to methodology, self‐disturbances research in schizophrenia tends to rely exclusively on verbal self‐report questionnaires and interviews. Given that individuals with schizophrenia suffer from language and communication difficulties, verbal self‐report measures may be insufficient. To bridge this gap, we have developed a new picture‐based instrument, the Benson et al. Body Disturbances Inventory (B‐BODI), designed to quantify bodily self‐disturbances with respect to the frequency and vividness of these experiences, as well as the degree of distress associated with them. Drawings that depicted different aspects of aberrant bodily self‐experiences were presented with accompanying captions. Participants were asked to indicate the frequency, vividness, and distressfulness of the experience captured by the picture using a 5‐point scale. Individuals with schizophrenia, older healthy controls, and college students participated in two alternative versions of the B‐BODI. Participants were also asked to complete a battery of established questionnaires that probed psychosis proneness and a range of self, body, and perceptual aberrations. The results suggest that the B‐BODI is a useful tool that accurately captures bodily self‐disturbances and has the potential to predict psychosis risk in healthy young individuals. Furthermore, anomalous self‐disturbances seem to be relatively stable across time in individuals with chronic schizophrenia.